Atomic Layer Deposited Non‐Noble Metal Oxide Catalyst for Sodium–Air Batteries: Tuning the Morphologies and Compositions of Discharge Product. (23rd March 2017) - Sun, Qian; Liu, Jian; Li, Xia; Wang, Biqiong; Yadegari, Hossein; Lushington, Andrew; Banis, Mohammad N.; Zhao, Yang; Xiao, Wei; Chen, Ning; Wang, Jian; Sham, Tsun‐Kong; et al.
Abstract : Catalysts can play a critical role in the development of sodium–air batteries (SABs). Atomic layer deposition (ALD) technology enables rational design and atomic utilization of catalyst by homogenously distributing catalytically active material on a variety of substrates. Here, a novel hierarchical nanostructured Co3 O4 is decorated on carbon nanotubes by ALD (CNT@Co3 O4 ) and used as a catalyst for SABs. CNT@Co3 O4 demonstrates better performance and longer cycle life than a mechanically mixed CNT/Co3 O4 nanocomposite. Well‐dispersed ALD Co3 O4 catalyst on CNTs, which serves as functionalized active sites, enables rapid electron exchange and high oxygen reduction/evolution activities. Synchrotron‐based X‐ray analysis including X‐ray absorption near edge structure, extended X‐ray absorption fine structure, and scanning transmission X‐ray microscopy characterization techniques have been employed to elucidate the activity of Co3 O4 and to investigate the nanoscale discharge product distribution found in SABs. This analysis reveals that Co3 O4 catalyst can promote the electrochemical decomposition of sodium peroxide, superoxide, and carbonates. The role of the catalyst in SABs is clarified and discussed in detail. Abstract : Atomic layer deposition (ALD) is applied for artificial rational design of the catalyst for Na–air batteries. The ALD carbon nanotube (CNT)@ Co3 O4 air electrode shows significantly improved oxygen evolution reaction and oxygen reduction reaction activities and extended cycling lives when compared to pristine CNT air electrodes and mechanically grinded CNT/Co3 O4 electrodes. The role of the catalyst in Na–air batteries is revealed and clarified.